Are there differences between perception of corruption at public and private sector? A multi-country analysis - Giorgina Piani
If we accept that the concept of corruption is influenced by culture and personal values then, we should ask: 1) what are the individual characteristics that shape corruption perception? 2) how important is the incidence of the country of residence in determining it? and 3) is there a relationship between private and public perception of corruption? The database is the 2007 GALLUP Public Opinion Survey; our dataset includes 78 countries and more than 57,000 observations and we estimated probit models. Our main conclusions are that some individual characteristics shape corruption perception (gender, age, marital status, the number of children, religion and religiosity). Moreover, country characteristics also matters. In particular, we find that Gross Domestic Product per capita and inequality play a relevant role. Finally, we also find that perception of corruption at public sector is highly correlated with perception of corruption at private sector.corruption, microeconomic behavior, cross-country comparative research.